2003
DOI: 10.1590/s0103-84782003000300007
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas lenhosas de pessegueiro cv. Okinawa em diferentes diâmetros de ramos, substratos e recipientes

Abstract: O trabalho foi desenvolvido no Departamento de Produção Vegetal - Setor Horticultura da Faculdade de Ciências Agronômicas (FCA) da Universidade Estadual Paulista "Júlio de Mesquita Filho" (UNESP), Campus de Botucatu (SP) com o objetivo de avaliar a influência de diferentes substratos e tipos de recipientes no potencial de enraizamento de estacas lenhosas de pessegueiro cultivar Okinawa com diferentes diâmetros. As estacas foram tratadas com 2,5g L-1 de ácido indol-butírico. O período de permanência das estacas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Other authors found different results, for example, TOFANELLI et al (2003) found a greater number of shoots in cuttings with a larger diameter of peach tree cv. Okinawa.…”
Section: Number Of Shoots and Shoot Lengthmentioning
confidence: 89%
“…Other authors found different results, for example, TOFANELLI et al (2003) found a greater number of shoots in cuttings with a larger diameter of peach tree cv. Okinawa.…”
Section: Number Of Shoots and Shoot Lengthmentioning
confidence: 89%
“…The results of this study indicated that perlite:peat (total porosity 70%, waterholding capacity 30%) and perlite (total porosity 75%, waterholding capacity 20%) are optimal for 'Gisela 5' hardwood cuttings. Tofanelli et al (2003) tested six rooting substrates (sand, carbonized rice husk, vermiculite, sand + carbonized rice husk, sand + vermiculite, and carbonized rice husk + vermiculite) for rooting of peach hardwood cuttings and found that the highest rooting frequency was obtained with vermiculite, independent of thickness. Denny and Arnold (2001) found the perlite substrate the best for the rooting of cuttings of american smoketree (Cotinus obovatus), whereas Ercisli et al (2002) found the highest rooting percentage for kiwifruit (Actinidia chinensis) hardwood cuttings was obtained in peat + perlite and peat + sawdust substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Many external factors such as cutting length and diameter, applied indole-3-butyric acid (IBA) concentration, date of cutting collection, and preheating can affect and increase rooting of hardwood cuttings of many species (Gill and Chitkara, 1990;Loach, 1988;Tofanelli et al, 2003) by influencing the endogenous auxin and carbohydrate contents of the tissues (Hartmann et al, 2002). Some bacteria such as those belonging to the genus Agrobacterium release auxin, can also have a positive effect on the rooting of cuttings (Sezai et al, 2003a(Sezai et al, , 2003b.…”
mentioning
confidence: 99%
“…Dutra e Kersten (1996) mencionam que quantidades equilibradas de água e ar, conferidos por drenagem adequada e maior espaço poroso favorecem o desenvolvimento de estacas. Tofanelli et al, (2003), verificaram em sua pesquisa que o equilíbrio na relação água/ar promovido pela vermiculita e areia foram favoráveis à brotação de estacas de pessegueiro 'Okinawa'. Timm et al (2015) constataram em seus estudos que a vermiculita média e a vermiculita média + areia demonstraram ser substratos adequados para a formação de mudas, por miniestaquia, de porta-enxertos de pessegueiro 'Okinawa', 'Flordaguard' e 'Nemared'.…”
Section: Substratosunclassified